Between sound metal and dross - Irmen, Kelley Diane, author; Steensen, Sasha, advisor; Beachy-Quick, Dan, 1973-, committee member; Lindsay, James E., 1957-, committee member (Colorado State University. Libraries, 2011)
Here is my fourth version of the book and this one directs itself and tells me to stop being confessional and to save my divulgence for another manuscript. This manuscript focuses on the relationship between the Vorarephile and the Exile - because he is no prophet, he is a wanderer who has been cut off from roaming. I continue the organization by eons, epochs, and theories, gaps in time, extinctions, and fossilization. As the book progresses, I bring in "the People" and I begin experimenting with the pronoun "I." Because for me, it is necessary that the "I" be fractured and in pieces, which means I, the author, am every era, character, place, or idea represented in this series. Initially, I was identifying with the Vorarephile, but as I continued in my re-ordering, I realized I am my exile, I caused my exile, and I've been exiled from exiling. Trust me; this makes sense, especially if you view exile as wandering, wandering as a way to escape, and then anxiety halting your fallback. So, let's say a person uses exploring the landscape in a nomadic-type fashion and suddenly is boxed in by all of the open space. Before, this space was a comfort and now, it is only a road and more roads and more roads, none of which I can ever turn of off.